ECONOMETRICS OF EXTREME VALUES IN ESTIMATING THE PML INDICATOR IN NATURAL CATASTROPHE (NATCAT) REINSURANCE (Scientific electronic journal "Labor Economics and Human Capital", 2026)
This research investigates the econometric modeling of the Possible Maximum Loss (PML) indicator to ensure the financial stability of the Uzbekistan insurance market under global climate change. Considering the specific agricultural and seismic risks of Uzbekistan, an integrated approach of Extreme Value Theory (EVT) and Quantile Regression is proposed. Analysis of NAPP and SNS Ratings data revealed that traditional methods underestimate risk by up to 24%. The paper provides scientifically grounded proposals for adapting the national insurance system to Solvency II international standards and optimizing reinsurance capital allocation.
Keywords: PML, NatCat, Solvency II, Extreme Value Theory, GPD distribution, Uzbekistan insurance market, Agricultural insurance, Quantile Regression.